Paradoxicality of the activity of institutional education institutions: principles and opportunities - Adolfas Juodraitis; Odeta Šapelytė (Social Welfare: Interdisciplinary Approach, 2014)
The article presents the problem of paradoxicality of the activity of juvenile institutional education (i.e., socialisation centres operating in Lithuania). Several important variables have not been considered in the interaction of the activities of the socialisation centre, simultaneously of pedagogical and other staff and learners, their families/foster parents, and this resulted in inconsistency of the implementation of the complex resocialisation process. The article calls for the scientific discussion, actualising essential principles of resocialisation observed in socialisation centres, grounded on empirical data of children’s subjective experience (N= 97) and assessment of specialists of the child socialisation centre (N=94).